Impacto da pandemia da covid-19 na saúde mental dos adolescentes de escolas públicas e privadas de Cascavel – PR - Lise, Andréa Maria Rigo (2024)
Objective: Identify the impact of the covid-19 pandemic in the post-pandemic period on the mental health of adolescents in public and private schools in the municipality of Cascavel, Paraná. Methodology: Integrative literature review and cross-sectional, quantitative, descriptive study conducted in public and private schools with 413 adolescents. Data were collected between May and August 2023, through a sociodemographic questionnaire developed by the study author, containing information such as: sex, age, participant's and their parents' education level, religion, family unemployment, COVID-19 cases in the family, need for hospitalization, practice of physical and/or recreational activities, internet usage hours, presence of positive/negative feelings, return to classes, emotional state, psychological/psychiatric follow-up, and application of the Depression, Anxiety, and Stress Scale for Adolescents (EDAE-A). Data were tabulated and analyzed using the statistical software R (version 4.3.3). Results: The sample used in this study consisted of 413 adolescents, with the majority being female (57.63%), aged between 12 and 18 years. Regarding symptoms of depression, stress, and anxiety, it was evidenced that 47.7% of adolescents had moderate, severe, or extremely severe levels of depression, 42.87% had moderate, severe, or extremely severe levels of stress, and 51.09% had moderate, severe, or extremely severe levels of anxiety. Female adolescents had a higher chance of presenting depressive and anxious symptoms. Adolescents who reported sleep difficulties had a higher chance of manifesting depressive symptoms, and regarding pandemic-related news, it was observed that the higher the exposure, the lower the chance of manifesting depressive symptoms. Regarding feelings during the pandemic, adolescents who reported positive feelings had a decreased chance of experiencing post-pandemic depression. Praying was a protective factor regarding the presence of anxious symptoms. Conversely, adolescents who had at least one unemployed parent during the pandemic, engaged in new activities during the pandemic - such as cooking, playing a musical instrument - had a higher chance of presenting anxiety levels. Adolescents who sought psychological and/or psychiatric care after the pandemic had a higher association with depressive and anxious symptoms after the pandemic period. Considerations: The COVID-19 pandemic has caused economic, social, psychological, and health consequences in the population, especially among adolescents, significant influence was noticed regarding symptoms of depression and anxiety.